Investment Strategies A Practical Approach to Enhancing Investor Returns - Jiang, Bill. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is a practical and unique investment resource designed to guide investors towards successful investing in the financial markets. It provides a selection of time-tested investment strategies to help investors enhance returns. Factor investing is positioned between active management and passive investing to combine their advantages. The book provides comprehensive coverage of common style factors such as quality and momentum in response to the rising investor interest in factor strategies. It presents a detailed description of the multifactor approach regarding its principle, investment merits and construction methods. The book also covers sustainable investing as it continues to rise in prominence across the investment sector. It employs an abundance of financial data, real cases and practical examples to help the audience understand different investment strategies in an interesting and informative way. The book is primarily written for private investors and investment practitioners such as equity analysts and investment advisors. It is also suitable for university students who are interested in learning practical investment strategies and traditional asset classes. Bill Jiang started his career as an Assistant Professor at the University of Birmingham before entering the industry. He has written 25 research papers in the areas of business management and software engineering. His research work has been published in International Marketing Review, Psychology & Marketing, Construction Management and Economics, Journal of Software: Evolution and Process, Journal of the Operational Research Society and other academic journals. Dr Jiang won the Best Paper award at the 2009 Annual Conference of Society for Marketing Advances in New Orleans. His research article in the Journal of Business & Industrial Marketing achieved the recognition as the most downloaded paper of the journal in 2012. Dr Jiang completed his doctoral research at Manchester Business School and received an MSc in Applied Statistics from the University of Oxford. He is a CFA charterholder and holds the Financial Risk Manager designation.
Investment Basics -- Asset Allocation -- Common Stock -- Bonds and Cash -- Precious Metals -- Size Effect -- Quality Investing -- Momentum Investing -- Value Effect -- Dividend Yield -- Volatility Effect -- Liquidity Premium -- Multifactor Investing -- Sustainable Investing -- Diversification -- Loss Control -- Fund Selection -- Passive Investing.
Keywords: Financial services industry; Capital market; Financial Services; Capital Markets